IMPROVING STUDENT LEARNING OUTCOMES IN THE SCIENCE SUBJECT OF ANIMAL CYCLE MATERIAL USING IMAGE MEDIA - Nifa Fauzia Mahesa, Yeni Sulaeman, Rifki Arif Nugraha (Jurnal Pendidikan dan Penelitian Serumpun Mendidik, 2024)
This research is classroom action research (PTK) collecting data using observation, testing and documentation techniques. Using the Kemmis and Mc Tagart model which begins with planning, action, observation and reflection, this research was carried out from April, May to June 2024 at in class IV of SDN Sukamanah 1, Jiput sub-district with a total of 15 students, consisting of 10 male students and 5 female students, this research consists of two cycles where each cycle is carried out in two meetings. The results of this research show an increase in student learning outcomes in the material animal life cycle, namely in the pre-cycle there were only 2 people who completed it with an average of 42.33 and a very low percentage of completion, namely 13.33%. In the first cycle, student results incr]eased from only 2 who completed the first cycle. became 9 with an average of 74.46 and a complete presentation of 60%. In the second cycle there was a significant increase from 9 students in the second cycle increasing to 14 students who completed with an average of 80.06 and a complete presentation of 93.33%. It can be concluded that using image media can improve student learning outcomes in animal life cycle material.